Exploring the relationship between code-switching and emotions. A systematic review. - Liu, Y (2023)
This systematic review aims to assess the interaction of code-switching (CS) and emotions, and how this relationship may be influenced by cross-cultural and cross-modality differences. The link between language preference and emotions has long been discussed, yet an overview on factors within and underlying the association is still lacking. As such, there is a critical need for a systematic evaluation of the interaction of CS and emotions. An initial search in four databases resulted in 1944 papers, which were then screened by 6 inclusion criteria. A total of 19 studies within the last 10 years were identified, with the majority of studies based in Asian contexts, and English as the most common second language. The overall risk of bias of included studies was moderate-to-high, and the key issue was the ambiguity of data collection. Narrative synthesis of selected studies showed that CS and emotions interacted with each other both in intrapersonal and interpersonal perspectives. People tended to switch their code when feeling emotional. CS was also applied for several affection functions, especially in expressing, negotiating, and managing emotions. Intensive, abrupt, and negatively charged emotions were often linked to CS, with anger being identified most frequently. This interaction could probably be either conscious or unintentional. Compared to people from western cultures, people originally from Asia were found applying CS uniquely for emotional support. No salient cross-modality difference was found. Overall, results of reviewed studies were consistent. Emotions could influence the occurrence of CS and CS was also employed for emotional functions. This interaction is influenced by personal language experiences that shaped by their social and cultural backgrounds. Further studies on other cross-linguistic and cross-cultural differences are suggested to build up the interaction to a broader context.